The Future of Hospitality and Tourism Profession - Tavares de Carvalho, P.; Monteiro, P. (VIII International Forum on Management: Abstracts, 2024)
Purpose – This study aims to understand how hospitality and tourism professionals and students see the future of their profession. Theoretical framework – In Portugal, Hospitality and Tourism sector is facing not only high turnover but also lack of human resources. In times of uncertainty, technological transitions and new cultures environment, the look for work life balance and well- being is a challenge for companies operating in the sector and crucial to retain talent and convince human resources to stay and improve competitiveness (Ping-Chao et al., 2020). “Work environment” significantly influence Generation Y employees’ job satisfaction, followed by “empowerment”, “pay”, and “relationships with managers”, that influences “employee commitment” and “intention to remain in hospitality business.” (Frye et al., 2020). Younger workers are rethinking their priorities and seeking jobs with a high purpose in search of harmony in their career and life, in their search for IKIGAI. Methodology – A questionnaire sent to Portuguese students and professionals working in the hospitality and tourism sector. Quantitative analysis with SPSS. Findings – The study will conclude about the opportunities, threats, motivational and demotivational factors to stay, believe or leave the sector in the future. Implications – Impact of recent variables such as Artificial Intelligence and new Human Resources Cultures concerning the future of hospitality and tourism profession. Originality – There are few studies in this subject.